On the microscopic theory of non-dissipative flows in Bose systems - Ivashin, A.P.; Poluektov, Yu.M. (Вопросы атомной науки и техники, 2007)
The states with non-dissipative flows are explored within a microscopic approach to a problem of spatially inhomogeneous multiparticle Bose-systems. Density of superfluid component was evaluated and its correlation with one- and two-particle Bose condensate density was analyzed also. На основі мікроскопічного підходу до опису просторово-неоднорідних багаточастинкових бозе-систем досліджено стан з незгасаючими потоками. Розраховано густину надплинної компоненти і проаналізовано ії зв’язок з густинами одночастинкового і парного бозе-конденсатів. На основе микроскопического подхода для описания пространственно-неоднородных многочастичных бозе-систем исследованы состояния со сверхтекучими потоками. Рассчитана плотность сверхтекучей компоненты и проанализирована ее связь с плотностями одночастичного и парного бозе-конденсатов.